Le « territoire tribal des Kurdes » et l’aire iraqienne (xe-xiiie siècles) : Esquisse des recompositions spatiales - Boris James (Revue des Mondes Musulmans et de la Méditerranée)
Since the very early stages of Arabic historiography in the ninth century, mention has been made of the Kurds by several authors. These Iranian populations, described as being fierce and rough, lived in the mountainous regions of the Middle East from Fârs to the Taurus. This area crossed by the Kurdish tribes is an always shifting ideal, tribal and political space. During the twelth century, Arabic medieval litterary sources seem to describe a reduction of what we call the “tribal territory of the Kurds”. This zone seems to slide westward the west and to overlap with the “Iraqi space”. This phenomena follows a political reshuffling born out of Turkmen infiltrations and the counter-crusades led by the Zankid rulers.